Solve the following inequalities: 2 x − 1 x + 1 > 3

tripes3h

tripes3h

Answered

2022-07-01

Solve the following inequalities:
2 x 1 x + 1 > 3

Answer & Explanation

Gornil2

Gornil2

Expert

2022-07-02Added 20 answers

2 x 1 x + 1 > 3
2 x 1 x + 1 3 1 > 0
2 x 1 x + 1 3 1 ( x + 1 ) ( x + 1 ) > 0
x 4 x + 1 > 0
x 4 = 0 x 2 4
x + 1 = 0 x = 1
x = 10 : 10 4 10 + 1 > 0
x = 2 : 2 4 2 + 1 > 0
x = 0 : 4 1 > 0
Solution: ( 4 , 1 )
Jeffrey Jordon

Jeffrey Jordon

Expert

2022-07-07Added 2575 answers

Answer is given below (on video)

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?